2014
DOI: 10.1177/1756287214528557
|View full text |Cite
|
Sign up to set email alerts
|

The role of cabazitaxel in the treatment of metastatic castration-resistant prostate cancer

Abstract: For decades, cytotoxic therapy was considered ineffective for the treatment of metastatic castration-resistant prostate cancer (mCRPC). Earlier therapies such as estramustine and mitoxantrone received regulatory approval based upon improvement in palliative endpoints. In 2004, docetaxel became the first treatment to demonstrate a significant survival benefit in patients with mCRPC based on two randomized phase III studies, TAX327 and SWOG 99-16. Cabazitaxel, a third-generation taxane, was chosen for clinical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 16 publications
(19 reference statements)
1
39
0
1
Order By: Relevance
“…Similarly, semisynthetic analogs of taxanes have been utilized in the development of several novel compounds with significantly higher efficiency against paclitaxel-resistant cancers. These include cabazitaxel (FDA approved) and ortataxel which have been shown to be efficient in hormone refractory metastatic prostrate cancer (81,82). Further, these compounds have been shown to be less amenable to efflux by P-gp.…”
Section: P-gp Substrate and Drug Interactionsmentioning
confidence: 99%
“…Similarly, semisynthetic analogs of taxanes have been utilized in the development of several novel compounds with significantly higher efficiency against paclitaxel-resistant cancers. These include cabazitaxel (FDA approved) and ortataxel which have been shown to be efficient in hormone refractory metastatic prostrate cancer (81,82). Further, these compounds have been shown to be less amenable to efflux by P-gp.…”
Section: P-gp Substrate and Drug Interactionsmentioning
confidence: 99%
“…U nemocných léčených kabazitaxelem jsme vzhledem k jeho hematologické toxicitě aplikovali primární profylaxi pegfilgrastimem. Profylaktická aplikace růstových faktorů významně redukuje riziko vzniku neutropenie a její komplikaci (HR 0,7; p = 0,04) [16]. Mezi rizikové faktory vzniku neutropenie stupně 3-4 patří věk nad 75 let, aplikace prvního cyklu a počet neutrofilů méně než 4 000/ mm 3 před podáním kabazitaxelu [17].…”
Section: Diskuzeunclassified
“…Docetaxel used in combination with other therapies has provided some promising results of progression-free survival. 7,11,12 Even so, some PCa becomes resistant to docetaxel and new treatment options are needed. Cabazitaxel was approved by the U.S. Food and Drug Administration (FDA) to treat docetaxel-resistant PCa, and works by targeting microtubules, altering the efflux pump in the cell (so that drug remains in the cell longer), and inducing apoptosis.…”
Section: Chemotherapymentioning
confidence: 99%
“…Cabazitaxel was approved by the U.S. Food and Drug Administration (FDA) to treat docetaxel-resistant PCa, and works by targeting microtubules, altering the efflux pump in the cell (so that drug remains in the cell longer), and inducing apoptosis. 12 Carboplatin (a platinum-based drug), and everolimus (an mTOR inhibitor) have been used in clinical trials as a combination therapy and have been shown to exert antitumor effects and to reduce prostate-specific antigen (PSA) levels. 7 Chemotherapy agents such as docetaxel can be beneficial for many patients with metastatic CRPC; however, more specific bone-targeting agents could help eliminate the adverse effects to other non-cancerous replicating cells throughout the patient's body.…”
Section: Chemotherapymentioning
confidence: 99%